The Urgence of the Criminalization of Trading in Influence in Corruption Eradication - Itok Dwi Kurniawan; Vincentius Patria Setyawan (Universitas PGRI Madiun, 2021)
Corruption has developed and is increasingly having a major impact on the life of the nation, state and society. Corruption is an act committed by a person or legal entity which is an act of abuse for personal or other people's interests that can harm state finances. Trading in influence is the answer to the development of patterns of handling corruption whose mode is growing from time to time. This article will discuss the regulation of trading in influence in positive law in Indonesia, and the regulation of trading in influence in the future to fill the legal vacuum in dealing with corruption. The writing of this article uses a normative legal research method by means of a literature study. The analysis used in this study is to use deductive analysis techniques. The approach used in this legal research is a conceptual approach and a statutory approach. The result of this study is to know about the urgency of adopting trading in influence norm that regulated in UNCAC to optimize in effort to eradicating corruption. The conclusion is trading in influence norm in UNCAC is very important to adopt in Indonesian Anti-Corruption Law because has wider range in corruption tracing..